A SYSTEMATIC REVIEW: THE INFLUENCE OF AGILITY, HUMAN RESOURCE FLEXIBILITY, AND ADAPTIVE LEADERSHIP ON EMPLOYEE RESILIENCE THROUGH PSYCHOLOGICAL CAPITAL - Ig Jarot Febri Setyo Wibowo; Budi Eko Soetjipto; Ludi Wisnu Wardhana (RADJA PUBLIKA, 2025)
Employee resilience has emerged as a strategic issue within the dynamics of modern organizations, which are increasingly marked by uncertainty and complex work-related pressures. This study aims to systematically synthesize recent literature on the influence of organizational agility, flexible human resource management, and adaptive leadership in fostering employee resilience, while also exploring the mediating role of psychological capital (PsyCap) as a key psychological mechanism. The method employed is a Systematic Literature Review (SLR), analyzing 32 scholarly articles from Scopus-indexed journals (Q1–Q4) published within the last five years. The findings reveal that structural agility, flexible HRM systems, and adaptive leadership collectively enhance workforce resilience through psychological empowerment and the development of individual psychological capital. PsyCap functions as a transitional mechanism that bridges organizational structures with personal adaptive capacity. Furthermore, this review identifies emerging thematic trends, such as the integration of agility–resilience–customer outcomes, and highlights theoretical gaps, particularly in multi-level and cross-sectoral approaches. The contribution of this study lies in the development of an integrative conceptual framework, combining structural, systemic, and psychological factors as the primary determinants of employee resilience, while offering strategic managerial recommendations for designing resilient and adaptive HRM systems. Another key implication is that strengthening internal organizational resilience has a significant impact on customer loyalty through improved service quality and employee resilience.